2018
DOI: 10.1017/s0266467418000329
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of phosphorus concentration in reproductive organs with soil phosphorus availability for tropical rain-forest trees on Mount Kinabalu, Borneo

Abstract: Abstract:Bornean rain forests on phosphorus (P)-poor soils exhibit a high P-use efficiency in the production of reproductive organs (i.e. the inverse of P concentration in reproductive-organ litter). The mechanism underpinning this high P-use efficiency is not known, but is hypothesized to result from dilution of P in a given type of reproductive organ and/or a shift of the community composition of flower/fruit types with decreasing P availability. These hypotheses were tested using eight forests with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Phylogenetic conservatism is another key aspect of the reproductive phenology of tropical trees (Bawa et al, 2003; Wright & Calderón, 1995). In the present study, the Myrtaceae showed supra‐annual cycles of flowering across sites (Figure 3a), although this family includes capsulate and fleshy‐fruited genera with different P demands for fruiting (Tsujii & Kitayama, 2018). Elevational variation in reproductive phenology was associated with taxa composition.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Phylogenetic conservatism is another key aspect of the reproductive phenology of tropical trees (Bawa et al, 2003; Wright & Calderón, 1995). In the present study, the Myrtaceae showed supra‐annual cycles of flowering across sites (Figure 3a), although this family includes capsulate and fleshy‐fruited genera with different P demands for fruiting (Tsujii & Kitayama, 2018). Elevational variation in reproductive phenology was associated with taxa composition.…”
Section: Discussionmentioning
confidence: 60%
“…This might be explained by efficient P utilization and acquisition, which may shorten the time required to accumulate resources. Among our study sites, it was reported that P concentration in reproductive organs decreased with soil P deficiency (Kitayama et al, 2015; Tsujii & Kitayama, 2018). This may reduce the P requirement per reproduction.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation